Nanoscale structural analysis of amorphous materials - McBride, W; Cockayne, D (2001)
Reduced density function (G(r)) analysis of energy filtered electron diffraction data provides structural information from small volumes of amorphous materials. Improvements in transmission electron microscopes, energy filters and data recording devices (CCDs) have made it possible to perform G(r) analysis from volumes as small as 1-2 nm in diameter.